ANALISA KECUKUPAN BESARAN IURAN PESERTA PROGRAM JAMINAN KESEHATAN PT ASKES (PERSERO) - , Surmiyati, DR. Drg. Julita Hendrartini, M.Kes., AAK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Commitment of the government to implement Act No. 40 issued in 2004 on National Social Insurance System and Act No. 24 issued in 2011 on National Social Administering Council is reflected from the appointment of PT. Askes as National Social Administering Council for Health that has to get prepared especially in budget adequacy and health service insurance package. Presently PT. Askes get participantsâ contribution based on percentage of salary but increase of salary is not followed by increase of cost of claim. Thus, it is necessary to analyze amount of contribution according to actual calculation and cost projection. Objective: To calculate amount of nett contribution of participants of PT. Askes health insurance program using contribution calculation approach based on claim data of PT. Askes in 2011 and to identify adequacy of PT. Askes contribution based on revenue of PT. Askes contribution in 2011. Method: This was a descriptive analytic case study with quantitative approach to analyze secondary data and qualitative approach obtained from in depth interview with the administrator of PT. Askes. Research instruments were secondary data of claim of PT. Askes participants in 2011. Result: Types of service of health insurance program covered by PT. Askes were primary outpatient, primary inpatient, secondary outpatient, and secondary inpatient. Based on data of claim in 2011 cost per individual was Rp 28,611.00. Amount of capitation for primary outpatient was Rp 2,660.00